Antibacterial Effect of Essential Oils (Clove Oil, Castor Oil and Ginger Oil) Against Human Pathogenic Bacteria - Dulal, Shraddha; Chaudhary, Sujan; Dangi, Chiranjibi; Sah, Shiv Nandan (International Journal of Applied Sciences and Biotechnology, 2021)
Essential oils are volatile, natural, complex compounds which are produced as secondary metabolites by plants for their protection against various microorganisms as well as pests. A wide range of plants have been explored for their essential oils in the past few decades. The study was conducted to determine the antibacterial activity of essential oils against human pathogenic bacteria which were gram positive (Staphylococcus aureus and Streptococcus pyogenes) as well as gram negative (Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Shigella sonnei). Five ml of three different oils, i.e. clove oil, castor oil, and ginger oil, were taken in a test tube so that each oil had four different concentrations. Four concentrations of (0, 25, 50 and 75) μL of oils were mixed with 1000, 975, 950 and 925 μL of DMSO respectively to make it a volume of 1ml. It was observed that clove oil was effective against the entire gram positive as well as gram negative bacteria that were used. The inhibition zone was greatest in the case of clove oil at 75 μL against P. aeruginosa (23 mm) and the smallest zone of inhibition was shown by castor oil against K. pneumoniae (12 mm). Other oils were sensitive as well as resistant to the bacteria. Hence, it is found that different oils have shown inhibitory activity towards different pathogens to a variable extent. However, clove oil was inhibitory to all the bacteria in all concentrations. Int. J. Appl. Sci. Biotechnol. Vol 9(4): 250-255